NOTAS SOBRE DICTYOTA PFAFFIIY D. HUMIFUSA (DICTYOTALES, PHAEOPHYTA) (Boletín de Investigaciones Marinas y Costeras, 2016)
Dictyota pfaffíi Schnetter and D. humifusa Hórnig, Schnetter et Coppejans are two small species whose taxonomic boundary is not clear. They are so similar, that there are not reasons to consider these two species from the Colombian Caribbean, living in the same environments, different.